Early colonization of macroalgae in an Atlantic Island subtidal rocky shore: an artificial vs natural substrata experiment. - Abreu, Maria H. (2013)
38th European Marine Biology Symposium. Aveiro, Portugal, 8-12 de Setembro de 2003.